2020
DOI: 10.1145/3401980
|View full text |Cite
|
Sign up to set email alerts
|

The Big Hack Explained

Abstract: Over the past two decades, globalized outsourcing in the semiconductor supply chain has lowered manufacturing costs and shortened the time-to-market for original equipment manufacturers (OEMs). However, such outsourcing has rendered the printed circuit boards (PCBs) vulnerable to malicious activities and alterations on a global scale. In this article, we take an in-depth look into one such attack, called the “Big Hack,” that was recently reported by Bloomberg Buisnessweek. The article provides background on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…For example, [18] proposes a placement defect detection approach using genetic algorithms while [19] proposes an approach using SURF and conventional morphological operations. A comprehensive survey of old and new hardware defect detection approaches can be found in [1,4]. In such methods, "defects" are defined in reference to a golden, i.e., non-defective, sample.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, [18] proposes a placement defect detection approach using genetic algorithms while [19] proposes an approach using SURF and conventional morphological operations. A comprehensive survey of old and new hardware defect detection approaches can be found in [1,4]. In such methods, "defects" are defined in reference to a golden, i.e., non-defective, sample.…”
Section: Related Workmentioning
confidence: 99%
“…Printed circuit boards (PCBs) are essential components of many contemporary electronic systems, ranging from private sector computers and cell phones to public sector military and medical equipment. Predominant developments in the outsourcing of PCB manufacturing make boards increasingly vulnerable on a global scale to malicious changes from external entities [1]. Attacks such as hardware Trojan insertions provide backdoor access to sensitive networks and compromise a nation's infrastructure, military capability, and civil safety.…”
Section: Introductionmentioning
confidence: 99%
“…To motivate the techniques’ application, consider how PCA boards are becoming increasingly complex and densely packed with small components, making the clean separation of foreground and background pixels increasingly challenging. Performing this accurately makes a big difference in the ability to automate the visual inspection of PCA boards and to facilitate counterfeit or security analyses [ 18 ]. By automating the segmentation of lesions from medical images, physicians will be able to detect abnormalities clearly and make more accurate diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric breakdown, electrical short circuit, and impedance mismatch are defects that can cause device failure [16]. These failures can be a product of manufacturing error or malicious alterations [6,17], but research has shown that it can be prevented through physical inspection using X-ray CT to perform dimensional analysis [17]. This dimensional analysis can be performed algorithmically based upon image processing techniques such as template matching between similar layers in the volume to segment the device's layer stack-up.…”
mentioning
confidence: 99%